Produksi perikanan pelagis yang didaratkan di TPI Selili, Kota Samarinda: Landing of capture pelagic fishery at TPI Selili, Samarinda City - Clara Frecilia Patiung; Irwan Ramadhan Ritonga; Ristiana Eryati (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2023)
Selili Fish Landed Place (TPI), Samarinda City has been built in 1900/1991 and served as an economic driver for fishing communities and ports in East Kalimantan Province. At TPI Selili, several types of pelagic fish have been landed based on the fish cached by the fisherman. However, some ordinary people in Samarinda city are not very familiar with pelagic fish names. Therefore, this study is needed to identification of pelagic fish landed at TPI Selili, Samarinda City. The purpose of this study was to identify the types of pelagic fish landed at TPI Selili. All data was collected at the TPI Selili, Samarinda City from September to October 2022. The methods used in this study were survey and interview methods. Identification of pelagic fish was conducted by matching the morphological forms of fish with fish identification books. All data from observations in the field were analyzed using Microsoft Windows Excel. All pictures and tables were described, described, and explained descriptively. It was found 6 species of small pelagic fish such as Indian scad fish, yellowtail scad, mackerel, gizzard shad, anchovies, sardines, and 3 species of large pelagic fish namely tuna, skipjack, and mackerel which landed in TPI Selili. In addition, the percentage of small pelagic fish that most landed at TPI Selili was Indian scad fish at 88.9%, and tuna at 96.1% for big pelagic fish.